Multicultural Bildungsroman: Coming of Age between Han and Sana - Reyes, Maria Luis Torres (Archīum Ateneo, 2024)
The paper explores ways in which the contemporary refunctioning of classical literary and cinematic genres might continue to provide vitality and relevance in building multi-faceted border-crossing societies such as multicultural communities. In the case of Korean hallyu cinema, Punch, the sleeper-hit film of 2011 about a Korean-Filipino character (“Kopino”), the “coming-of-age” genre is located at the nexus between the key features of the Bildungsroman and the project of multiculturalism in dominantly monocultural Korea. In the process of refunctioning, the aesthetics of the film is reworked from a narrative structured by the integrative logic of an individual’s development (Bildungsroman) into a political site for negotiation of contentious tensions (multiculturalism). As a “hybrid” Korean film characteristic of many products of the hallyu culture industry, at its contact zone is the Kopino (Korean-Filipino), the main protagonist, Wan-deuk, at which the structure of the Bildungsroman, the Korean han and the Filipino affect sana become resilient and dynamic if not always visible features that textually coalesce and collide in the process of “generic translocality,” multiplying the tensions and reframing the narrative structure. The result is the emergence of a refunctioned hybrid genre toward what might be called the “multicultural Bildungsroman” in Punch.